2016
DOI: 10.1103/physrevlett.117.084801
|View full text |Cite
|
Sign up to set email alerts
|

In SituObservation of Dark Current Emission in a High Gradient rf Photocathode Gun

Abstract: Undesirable electron field emission (a.k.a. dark current) in high gradient RF photocathode guns deteriorates the quality of photoemission current and limits the operational gradient. To improve the understanding of dark current emission, a high-resolution (∼100 µm) dark current imaging experiment has been performed in an L-band photocathode gun operating at ∼100 MV/m of surface gradient. Dark current from the cathode has been observed to be dominated by several separated strong emitters. The field enhancement … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Diagnostics used in the experiment include three directional couplers to monitor the input, reflected, and transmitted rf signals and two Faraday cups to collect upstream and downstream dark currents during rf conditioning. These signals were monitored pulse by pulse for breakdown detection [17,38,39]. Normal rf pulse signal and typical breakdown signal are shown in Fig.…”
Section: B Conditioning Strategymentioning
confidence: 99%
“…Diagnostics used in the experiment include three directional couplers to monitor the input, reflected, and transmitted rf signals and two Faraday cups to collect upstream and downstream dark currents during rf conditioning. These signals were monitored pulse by pulse for breakdown detection [17,38,39]. Normal rf pulse signal and typical breakdown signal are shown in Fig.…”
Section: B Conditioning Strategymentioning
confidence: 99%
“…Many studies [1][2][3][4][5][6] have convincingly demonstrated that the electron emission from a large surface area field emission cathode placed in a macroscopic electric field E is not uniform. The emission area is only a small portion of the total surface area of a cathode since most of the emission is confined to a small number of emission spots randomly distributed over the cathode surface.…”
Section: Introductionmentioning
confidence: 99%
“…Second is fundamental: only a properly established j-E (and not I-V ) relationship can be used to define the validity range of a classical Fowler-Nordheim (FN) emission and clarify the role of other mechanisms that could cause deviation from the FN emission, i.e. cause non-conventional behavior that is being observed across a large body of experimental work [1][2][3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [1][2][3][4][5][6] have convincingly demonstrated that electron emission from a large surface area field emission cathode placed in a macroscopic electric field E is not uniform. The area contributing to emission is only a small portion of the total surface area available for emission.…”
Section: Introductionmentioning
confidence: 99%
“…Second is fundamental: only a properly established j-E (and not I-V ) relationship can help define the validity range of a classical Fowler-Nordheim (FN) emission and clarify the role of other mechanisms at play that cause deviation from the FN emission, i.e. cause nonconventional behavior, that is have being observed across a large body of experimental work [1][2][3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%